CompTIA A+ Core 1 (220-1101). - Prowse, David L. (Complete video course (Pearson IT)., 2022)
35+ Hours of Video Instruction Overview More than 35 hours of video instruction covering all topics on the CompTIA A+ Core 1 (220-1101) exam. Overview CompTIA A+ Core 1 (220-1101) Complete Video Course (Video Training) features 35 hours of video training that serves as your complete resource to get exam ready for the updated CompTIA A+ Core 1 (220-1101) exam. The course acts as a full study resource so you can gain a solid understanding of A+ skills. David L. Prowse provides a hands-on approach to learning, covering all objectives in the exam but also going deeper with demos and labs--both live-action hardware and virtual software--so you can see in real time how to troubleshoot and fix real hardware, software, and network problems. CompTIA A+ Core 1 (220-1101) Complete Video Course (Video Training) contains 32 lessons that start with an overview of mobile devices, networking, hardware, and software analysis, including storage devices, CPUs, motherboards, add-ons, printers, etc., before covering virtualization, cloud computing, hardware, and network troubleshooting. While other courses teach with slides only, best-selling author David L. Prowse gives you the real-world training you need by Examining hands-on configuration labs in real time Exploring troubleshooting techniques: highlighting how to determine and then fix common problems that you'll find on the exam and in your work Building a computer live on camera so you can see first-hand how to accomplish this key task Topics include Module 1: Mobile Devices Module 2: Networking Module 3: Hardware Module 4: Virtualization and Cloud Computing Module 5: Hardware and Network Troubleshooting About the Instructor David L. Prowse is an author, technical trainer, and technology problem solver. His titles for Pearson include previous editions of the CompTIA A+ Exam Cram, CompTIA A+ Complete Video Course, and CompTIA A+ Practice Questions. He supports his products and answers questions at his website: https://dprocomputer.com. Skill Level Intermediate to Advanced Learn How To Install and configure laptop hardware Compare, contrast, connect, and configure mobile devices Troubleshoot motherboards, CPUs, RAM, hard drives, RAID arrays, video, and mobile devices Use network tools such as twisted-pair cabling and testing tools, patch cable, loopback cables, and Wi-Fi analyzers Configure networking: IPv4, IPv6, subnet masks, VLAN, etc. Who Should Take This Course Anyone looking to pass the CompTIA exam Anyone interested in entering the IT field Current computer technicians, help desk technicians, and LAN support specialists About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.